Light industry companies of Ukraine: overview and analysis of baseline conditions - Yulia Nefedova; Yulia Olifirova (Cхід)
The paper reviews and analyzes the baseline conditions of light industry companies: the nature and structure of the branch is covered, the economic downturn which is legacy of the economic complex of the Ukrainian Soviet Socialist Republic described, statistical key figures and other dynamic indicators of the current development of the industry reviewed, a complex of outstanding problems impeding its efficient development outlined. There are main constraints on the way to attraction of foreign and domestic investment in the branch identified.